2015
DOI: 10.1103/physrevc.91.034313
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit decomposition ofab initionuclear wave functions

Abstract: Although the modern shell-model picture of atomic nuclei is built from single-particle orbits with good total angular momentum j, leading to j-j coupling, decades ago phenomenological models suggested a simpler picture for 0p-shell nuclides can be realized via coupling of total spin S and total orbital angular momentum L. I revisit this idea with large-basis, no-core shell model (NCSM) calculations using modern ab initio two-body interactions, and dissect the resulting wavefunctions into their component L-and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 58 publications
5
56
0
1
Order By: Relevance
“…(S p S n S) Probability, % (λ 0 µ 0 ) Probability, % Probability, % (λ 0 µ 0 ) (λ µ)* 6 Li ( A more recent study [254] using SRG effective interactions in the NCSM has arrived at the same conclusions, while, in addition, it points to a similar spin pattern in odd-A p-shell nuclei.…”
Section: Nucleusmentioning
confidence: 48%
“…(S p S n S) Probability, % (λ 0 µ 0 ) Probability, % Probability, % (λ 0 µ 0 ) (λ µ)* 6 Li ( A more recent study [254] using SRG effective interactions in the NCSM has arrived at the same conclusions, while, in addition, it points to a similar spin pattern in odd-A p-shell nuclei.…”
Section: Nucleusmentioning
confidence: 48%
“…4 That the ab initio calculated negative parity rotational band members of 9 Be largely obey LS coupling was demonstrated in Ref. [18], in the context of calculations with the Entem-Machleidt N 3 LO interaction. The portion of any NCCI calculated wave function coming from contributions with a given L or S is not manifest from its expansion in a tradititional M -scheme basis, but the so-called "Lanczos trick" 5 may be used to decompose the original calculated wave function into con- 4 In the context of the shell model, where the strength of the spin-orbit interaction controls the transition from LS to jj coupling, these schemes are termed the weak coupling and strong coupling regimes, respectively [62].…”
Section: Angular Momentum Structurementioning
confidence: 91%
“…Some of these rotational bands (or portions thereof) have been studied before in NCCI calculations [13][14][15][16]18]. However, these earlier calculations, which were based on internucleon interactions such as JISP16 [19] and NNLO opt [20], suffered from a significant limitation: excited rotational bands were relatively poorly converged in the many-body calculations, lying at much higher excitation energy than they would either in a more completely converged calculation for those interactions or, indeed, in experiment.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence the low-dimensional unitary groups SU(2), SU(3) and SU(4) come into the game. The tens of years of application of the shell model have shown that the simplest shell model configurations play a very important role as being in many cases the main components of the nuclear wave function [28]. The wave functions constructed using the quantum numbers of the permutation and unitary groups are very suitable for analysis of the possible cluster decomposition of the state of hyperfragment formed in the reaction and they give a possibility to calculate preformation factors for various decay channels.…”
Section: Tismmentioning
confidence: 99%